PERAN SPIRITUALITAS DITEMPAT KERJA SEBAGAI MEDIASI PENGARUH PENERAPAN KEPEMIMPINAN SPIRITUAL TERHADAP KINERJA PEGAWAI DI BALAI PEMASYARAKATAN KELAS II KENDARI - Wulandary Wulandary; La Hatani; Muhammad Masri; Ansir Ansir; Nursaban Rommy; Muhammad Taufik; Enny Wati (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This research was conducted with the aim of examining and explaining the influence of spiritual leadership, workplace spirituality on employee performance and examining and explaining the role of spirituality in the workplace as a mediation for the influence of spiritual leadership on employee performance. This type of research is a quantitative approach with this type of explanatory research. The population in the study were all employees of the Kendari Class II Correctional Center, totaling 61 employees not including the leadership. The sampling technique was carried out by means of a census, meaning that the object of research was all the employees of the Kendari Class II Correctional Center. Analysis using structural equation modeling (SEM) using the SmartPLS version 3.2 program package. The results showed that spiritual leadership had a significant positive effect on employee performance. Spiritual leadership has a significant positive effect on spirituality in the workplace. Spirituality in the workplace has a significant positive effect on employee performance and Spirituality in the workplace plays a role in mediating the influence of spiritual leadership on employee performance.